2022
DOI: 10.3390/ijerph192416674
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Biotopes, Listeners and Sound-Induced Action: A Case Study of Operating Rooms

Abstract: As socio-technological environments shape and direct listener behaviour, an ecological account is needed that encompasses listening in complexity (i.e., multiple listeners, multiple sounds and their sources, and multiple sound-induced actions that ensure the success of a mission). In this study, we explored sound-induced action under the framework of “acoustic biotopes” (a notion of ecological acoustics by Smolders, Aertsen, and Johanessma, 1979 and 1982) in a specific socio-technological environment, i.e., th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 90 publications
0
11
0
Order By: Relevance
“…The field survey of the soundscape and emotional perception in the pediatric dentistry clinic was divided into two parts, i.e., interviews and field questionnaires. According to the concept of acoustic biotopes ( Özcan et al, 2022 ), a dental clinic is viewed as a biotope, with species including healthcare workers and young pediatric patients. Therefore, based on different audience groups, respondents in the pediatric dental clinic were categorized into two groups for the interviews conducted in Chinese: healthcare workers and young pediatric patients; young pediatric patients were interviewed and surveyed with the accompaniment of their family members.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The field survey of the soundscape and emotional perception in the pediatric dentistry clinic was divided into two parts, i.e., interviews and field questionnaires. According to the concept of acoustic biotopes ( Özcan et al, 2022 ), a dental clinic is viewed as a biotope, with species including healthcare workers and young pediatric patients. Therefore, based on different audience groups, respondents in the pediatric dental clinic were categorized into two groups for the interviews conducted in Chinese: healthcare workers and young pediatric patients; young pediatric patients were interviewed and surveyed with the accompaniment of their family members.…”
Section: Methodsmentioning
confidence: 99%
“…The age range of the pediatric patient sample in this study was controlled to be between 0 and 11 years old (the interview outline is shown in Table 1 ). What people hear depends on who is listening, and the way people listen can affect the likelihood of interacting with different components of the environment ( Özcan et al, 2022 ). Therefore, based on the results of the interviews, the pediatric dental clinic includes 10 types of sound sources.…”
Section: Methodsmentioning
confidence: 99%
“…One of the main causes of the problem is that hospitals offer shared acoustic spaces (i.e. acoustic biotopes) in which multiple actors (patients, visitors, and healthcare providers) and multiple objects (healthcare devices, medical tools) interact and contribute to the overall quality of the acoustic environment [9]. Such shared spaces also have different functions, which can change over the time of the day.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a patient room should be conducive to caregiving activities as well as resting and sleeping. Because of the ambiguity of its functions, it may be difficult to organise the acoustic environment or control the sound-producing events, especially because nurses are often unaware of the sonic consequences of their and others' actions [9]. Thus, mitigating the problem of sleep disruption by sound is an ongoing effort in the field of sound-driven design for healthcare [10] [11].…”
Section: Introductionmentioning
confidence: 99%
“…Noise in Operating Rooms (OR) is a widely acknowledged issue and listening in the OR is an active but also a collective experience in an acoustic environment which patients and OR staff members coexist [1]. In orthopedic surgeries specifically, medical staff has an average exposure to excessive noise of 19-37 minutes and the equivalent sound pressure can be around 66.5 dBA [2] with peaks reaching 120-140 dBA [1].…”
Section: Introductionmentioning
confidence: 99%